The Effect of E-Commerce on Social Networks and Consumer Dependence among University of North Sumatera (USU) Students - Harahap, Rahma Hayati; Nahampun, Tiffanyia; Jasmine, Humaira (Journal Business Administration: Entrepreneurship and Creative Industry, 2025)
This research aims to evaluate and study the impact of e-commerce on social networks and the level of dependency of USU students. This research involves surveys and data analysis from USU students who actively use e-commerce platforms. The results of this research show that e-commerce has a positive effect on expanding USU students’ social networks, with increased social interaction through this platform. In addition, this research shows that USU students tend to become more dependent on e-commerce in the shopping process and interacting with available products and brands. Therefore, it is important to better understand the use of e-commerce by college students and its impact on social networks and consumer behavior.